BƯỚC ĐẦU KHẢO SÁT LÝ THUYẾT CƠ CHẾ PHẢN ỨNG CỦA GỐC ETINYL VỚI METANOL - Trị, Trần Quốc; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
The reaction mechanism of the ethynyl radical (C2H) with methanol (CH3OH) has been studied by the Density Functional Theory (DFT) using the B3LYP functional in conjunction with the 6-311++G(d,p) and, 6-311++G(3df,2p) basis sets. The potential energy surfaces describing these processes were been constructed. The products of (C2H2 +CH2OH), (C2H2+CH3O), (HCCCH3+OH), (H2CC+CH2OH), (HC(C)CH3+OH), (HCCOH+CH3), (CCHOH+CH3), (H2CC+CH3O), (HCCCH2OHtrans+H), (HCCCH2OHcis+H), (HC(C)CH2HO+H), (C2H3+CH2O) can be found. However, the present work indicates that the formation of (C2H2+CH2OH), (C2H2+CH3O) is the most favorable. Our results contribute to a more complete understanding about the reaction mechanism of the C2H radical with CH3OH.